Pengaruh Inventory Turn Over, Debt to Equity Ratio, dan Earning Per Share Terhadap Harga Saham dengan Ukuran Perusahaan Sebagai Variabel Moderasi pada Perusahaan Sektor Energi yang Terdaftar di Indeks Saham Syariah Indonesia - Heru Nurmiaswari; Andry Priharta; Riyanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to test and analyze the effect of inventory turnover, debt-to-equity ratio, and earnings per share on stock prices with company size as a moderating variable in energy sector companies listed on ISSI. The population in this study was 68 energy sector companies listed on ISSI. The sample determination in this study used a purposive sampling method with a sample size of 14 companies, with an observation period of 5 years. The data analysis technique in this study used panel data regression using the Eviews Version 13 application. The results of this study stated that inventory turnover and debt-to-equity ratio had a positive but insignificant effect while earnings per share had a significant positive effect on stock prices. Company size does not moderate the impact of inventory turnover and debt-to-equity ratio but can moderate the effect of earnings per share on stock prices.